2002
DOI: 10.1021/tx0101090
|View full text |Cite
|
Sign up to set email alerts
|

Structure of an Oligodeoxynucleotide Containing a 1,N2-Propanodeoxyguanosine Adduct Positioned in a Palindrome Derived from the Salmonella typhimurium hisD3052 Gene:  Hoogsteen Pairing at pH 5.2

Abstract: The structure of the 1,N(2)-Propanodeoxyguanosine (PdG) adduct was determined at pH 5.2 in the oligodeoxynucleotide duplex 5'-d(CGCGGTXTCCGCG)3'.5'-d(CGCGGACACCGCG)-3' (X = PdG). This sequence, referred to as the -TXT- sequence, is contained within the Salmonella typhimurium hisD3052 gene and contains a palindrome, representing a potential hotspot for frameshift mutagenesis. PdG provides a model for the primary adduct induced in DNA by malondialdehyde, the 3-(2'-deoxy-beta-D-erythro-pentofuranosyl)pyrimido[1,2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
46
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 60 publications
5
46
0
Order By: Relevance
“…1). Nuclear magnetic resonance studies of the ring-closed form, 1,N 2 -propano-2Ј-deoxyguanosine (PdG), have shown that, in duplex DNA, the adducted base assumes a syn conformation and forms a PdG (syn) · dC ϩ (anti) Hoogsteen base pair with a C (22,29). The ring-open form of ␥-HOPdG, N 2 -(3-hydroxypropyl), remains in the anti conformation and retains the ability to form a normal Watson-Crick base pair with the C (4,13,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1). Nuclear magnetic resonance studies of the ring-closed form, 1,N 2 -propano-2Ј-deoxyguanosine (PdG), have shown that, in duplex DNA, the adducted base assumes a syn conformation and forms a PdG (syn) · dC ϩ (anti) Hoogsteen base pair with a C (22,29). The ring-open form of ␥-HOPdG, N 2 -(3-hydroxypropyl), remains in the anti conformation and retains the ability to form a normal Watson-Crick base pair with the C (4,13,14).…”
mentioning
confidence: 99%
“…Since ␥-HOPdG is expected to be in the closed cyclic form when it is the templating residue (15,21), Pol can incorporate a C or a T opposite this adduct because of its ability to accommodate the closed cyclic form and utilize the Hoogsteen edge of the modified base that would be in a syn conformation (22,29). Pol proficiently extends from the dCMP residue, but not from the dTMP residue, incorporated by Pol opposite ␥-HOPdG, presumably because the incorporation of dCMP but not of dTMP favors the ringopening reaction of ␥-HOPdG (4,16), and the ability of the ring-opened adduct to form a normal Watson-Crick pair with the C (4) enables Pol to extend from such a primer terminus.…”
mentioning
confidence: 99%
“…1). The nuclear magnetic resonance studies of a PdG present in the duplex DNA have shown that the adducted base adopts a syn conformation and forms a PdG(syn) · dC ϩ (anti) Hoogsteen base pair with the opposing C (18,27).…”
mentioning
confidence: 99%
“…The saturated analogue 1,N 2 -propanodG (PdG adduct) (49) was used by our laboratory (30,(50)(51)(52)(53)(54) as well as by other laboratories (55-58) as a stable structural surrogate for exocyclic 1,N 2 -dG adducts such as the M 1 dG adduct and the acrolein γ-OH-PdG adduct. The PdG adduct reduced the thermal stability, transition enthalpy, and transition free energy of duplex DNA when positioned opposite dC or dA (59).…”
Section: Discussionmentioning
confidence: 99%